IMPLEMENTING MIND MAPPING TECHNIQUE IN THE PROCESS-BASED APPROACH TO TEACH WRITING HORTATORY EXPOSITION TEXT - Badriyah, Siti Syarifatul (2015)
Abstract This study investigates how the implementation of mind mapping technique in the process-based approach can help students to write a Hortatory Exposition text in one senior high school in Bandung. This study also analyzes students' responses towards the implementation of mind mapping technique in the process-based approach to teach writing a Hortatory Exposition text. This study employs a descriptive-qualitative case study research design. The data were obtained from classroom observation, students' writing product analysis, and interview with students. To gain the results from students' writing products, nine diagnostic texts and nine final writings from nine students representing low-, middle- and high- achieving students were analyzed in terms of the description of schematic structures, including the analysis of idea organization specifically in the argument stage, and linguistic features of Hortatory Exposition text as proposed by Derewianka (2004), Emilia (2010, 2012), Gerot and Wignell (1994), Knapp & Watkins (2005). The analysis is on the basis of SFL Theme System including Theme choice and Theme progression pattern as proposed by Gerot and Wignell (1994), Halliday (1994), and Eggins (2004). The results reveal that the implementation of mind mapping technique in the process-based approach could help students to write a Hortatory Exposition text, especially in the prewriting stage in which the students generate and organize ideas to build up convincing and logical arguments. In addition, the interview data reveal that generally the students expressed their positive responses towards the implementation of mind mapping technique in the process-based approach especially in the prewriting stage in which they generated and organized ideas they wanted to include in their Hortatory Exposition text. Nevertheless, grammatical mistakes were still found in the low- and middle-achieving students' texts, indicating that mind mapping technique in the process-based approach could not maximally contribute to the improvement in terms of grammar and linguistics features. Based on the findings, it is recommended that the mind mapping technique should be implemented in teaching writing different genres by incorporating at least two approaches that emphasize both process and genre pedagogy.